In-process grinding wheel wear evaluation using digital image processing. (31st July 2019) - Azarhoushang, Bahman; Ludwig, Sebastian
The microtopography of the grinding tool surface is essential for the result of the grinding process. Micro wear and tool loading lead to an increase in process forces and temperatures. Subsequently, poor surface qualities, dimensional and profile errors and thermal damage to the workpiece could be induced by the grinding process. A novel process-oriented measuring method is developed to quickly and efficiently evaluate the surface topography of grinding tools. Images of the tool surface are evaluated by an innovative image processing software for characterising grit flattening and tool loading. The developed technique and the results of the application during the grinding process is described. The results show a direct proportionality between the output values of the proposed method and the measured grinding forces. Hence, the developed measurement method can be used for the evaluation of grinding process and for an assessment of the tool life.